Situational diagnosis performed in ESF 303 (International Seven Journal of Health Research, 2024)
The Family Health Strategy (ESF) is crucial to expanding health coverage. This study, carried out by the second term of the Medicine course at the Centro Universitário de Goiatuba, analyzed the Family Health Strategy - 303, in Goiatuba, through situational diagnosis, which assesses the health conditions of a population, allowing us to know the challenges experienced in that place and plan strategic actions for possible improvements. Goiatuba, in Goiás, has 13 Family Health Units serving 35,664 inhabitants. Data from the health unit was collected and analyzed, including interviews with the preceptor and nurses, as well as site visits. A prevalence of cases of hypertension, diabetes and schizophrenia was observed, as well as structural weaknesses such as the lack of a vaccination room, a preventive care room, problems in the dental office and the absence of a full team of collaborators. These factors hamper the efficiency of the service and the quality of care. Pamphlets were distributed and an awareness campaign on healthy lifestyles was carried out, encouraging healthy eating, physical exercise and structural improvements to the unit were suggested, such as implementing psychological counseling. The research highlighted the importance of situational diagnosis in order to understand the reality of local health and implement more effective actions aimed at serving the entire population.